O-286 Bisphenol A in blood serum and follicular fluid of women undergoing to cycle of IVF living in areas with different environmental impact. (EcoFoodFertility Project). (30th June 2022) - Gentile, M; Raimondo, S; Gentile, R; Gentile, T; Fortunato, A; Piscopo, M; Crescenzi, C; Siani, L; Ferrara, I; Esposito, A; Iaccarino, M; Notari, T; et al.
Abstract: Study question: Bisphenol A (BPA) is a constituent of polycarbonate and epoxy resin plastics and is also a by-product of combustion of plastics, resulting harmful for health. Summary answer: To evaluate the presence of BPA in the blood and Follicular Fluids, in women, subjected to IVF cycles, living in areas with different environmental impact. What is known already: BPA is used in the production of polycarbonate plastics and epoxy resins. 1, 3, 5-triphenylbenzene is a tracer for burning plastic and has been related to levels of bisphenol A in the air, so the actual release of bisphenol A to the atmosphere could result from burning the plastic. Bisphenol A belongs to the group of endocrine disruptors. Little is known about the effects of BPA on human female reproduction. BPA levels appear to be inversely related to the number of oocytes retrieved in IVF cycles, and it also appears to negatively affect the ovulatory peak of estradiol. Study design, size, duration: In the frame of EcoFoodFertility project a cross sectional study conducted in Campania Region (Southern Italy), between January 2019 and December 2020, 74 women, no smokers, no chronic diseases, not exposed to occupational risk factors. living for at least 5 years in areas with low environmental impact (LEI, 31 women), Alto-Medio Sele in province of Salerno and high environmental impact (HEI, 43 women), so-called "Land of Fires" in province of Naples, were selected. Participants/materials, setting, methods: Participants have a normal ovarian reserve, average age 32.05 + 3.49, with infertility duration between 26 and 39 months and at the first experience of an IVF cycle. ELISA was used for measuring bisphenol A in blood and Follicular Fluids (FFs), expressed in ng/ mL. 5 mL glass tubes, without additives, not siliconized and kept in a horizontal position were used. FFs were bloodless with a negative albumin test. Main results and the role of chance: Differents levels of BPA were found in all processed samples. In the LEI (Low Environmental Impact) group, serum levels vary from a minimum of 3.1 ng/mL to a maximum of 7.7 ng/mL (4.1 ± 1.6) and the Follicular Fluids levels vary from a minimum of 7, 1 ng/mL to a maximum of 55.3 ng/mL (13.8 ± 10.9). In the HEI (High Environmental Impact) group, serum levels vary from a minimum of 69.2 ng/mL to a maximum of 167.8 ng/mL (95.5 ± 24.3) and Follicular Fluids levels vary from a minimum of 4.2 ng/mL to a maximum of 34.3 ng/mL (19.9 ± 9.2). Statistical processing of the data shows a highly significant variation in serum levels (p < 0.0001) with higher values in the HEI group (95.5 ± 24.3) than in the LEI group (4.1 ± 1.6). A moderately significant change (p < 0.01) for Follicular Fluids levels, higher in the HEI group (19.9 ± 9.2) than in the LEI group (13.8 ± 10.9). Furthermore, the data did not show any correspondence between serum and Follicular Fluids for any of the participants tested. Limitations, reasons for caution: The ELISA method for the determination of BPA seems suitable to us, however, the subject requires further biomonitoring studies, with a larger sample and greater selection of participants, to better understand the effects of BPA and its metabolites in FF and in other districts of the female reproductive system. Wider implications of the findings: The results indicate that the greater bioaccumulation in women of the HEI group appears consistent with the environmental condition of the area and with the comparative studies already carried out within the EcoFoodFertility project. This is further evidence that pollution in this area can interfere with female fertility and beyond. Trial registration number: G003